Sosialisai peluang karier di Jepang untuk meningkatkan daya saing lulusan SMK Pertanian di Pekanbaru - Nur 'Izzati; Arza Aibonotika; Dini Budiani; Fatmawati Andini; Merri Silvia Basri; Nana Rahayu; Hana Nimashita (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
This Community Service activity aims to provide education, build motivation, and enhance the understanding of agricultural vocational high school (SMK Pertanian) students and teachers in Pekanbaru regarding employment opportunities in Japan through the Specified Skilled Worker (SSW) program. This initiative was undertaken in response to the Japanese government's decision to open up job opportunities for foreign workers. This policy remains relatively unknown among prospective graduates of agricultural vocational schools in Indonesia. The methods used in this activity included seminars, material presentations, interactive discussions, and questionnaires to assess participants' understanding and responses. The results showed that most participants lacked sufficient knowledge about job opportunities in Japan but demonstrated high enthusiasm to learn more. Based on the evaluation, the activity was considered successful in broadening participants' insight into career prospects in Japan and encouraging them to better prepare for the global job market.